Role of anterior segment optical coherence tomography angiography in the assessment of acute chemical ocular injury : a pilot animal model study - Tey, Kai Yuan (2021)
To examine the use of anterior segment-optical coherence tomography angiography (AS-OCTA) in the assessment of limbal ischemia in an animal model chemical ocular injury. We conducted a prospective study using an established chemical ocular injury model in 6 rabbits (12 eyes), dividing the cornea limbus into 4 quadrants. Chemical injury grade was induced based on extent of limbal injury (0 to 360 degrees) and all eyes underwent serial slit-lamp with AS-OCTA imaging up to one month. Main outcome measure was changes in AS-OCTA vessel density (VD) comparing injured and control cornea limbal quadrants within 24 h and at one month. AS-OCTA was able to detect differences in limbal VD reduction comparing injured (3.3 ± 2.4%) and control quadrants (7.6 ± 2.3%; p < 0.001) within 24 h of ocular chemical injury. We also observed that AS-OCTA VD reduction was highly correlated with the number of quadrants injured (r = - 0.89; p < 0.001; 95% CI - 5.65 to - 1.87). Corneal vascularization was detected by AS-OCTA in injured compared to control quadrants (10.1 ± 4.3% vs 7.0 ± 1.2%; p = 0.025) at 1 month. Our animal pilot study suggests that AS-OCTA was able to detect limbal vessel disruption from various severities of acute chemical insult, and in the future, could potentially serve as an adjunct in providing objective grading of acute ocular chemical injury once validated in a clinical trial.